Complexation process and binding parameters of curcumin and short amylose with V7-type helix structure - Xiaojing Li; Lei Dai; Jie Zhong; Tingting Li; Gongjian Fan; Dandan Zhou; Caie Wu (Grain & Oil Science and Technology)
Pre-formed V7-type short amylose (SA) could interact with curcumin to form inclusion complex (IC) thereby to improve the stability of curcumin. However, the complexation mechanism of V7-type SA and curcumin is not clear, which limit the improvement of inclusion efficiency. To obtain a starch nanocarrier with high loading capacity, the encapsulation process and interaction parameters of V7-type SA-curcumin IC was studied. The analysis results demonstrated that stoichiometric ratio value of the SA-curcumin complex was around 1. V7-type SA performed excellently in the delivery of curcumin attributing to their high loading capacity (over 20%). It was found that curcumin could enter into the pre-formed helical cavity of SA to form an IC. The conformation change of SA caused the reduction in the interaction ratio in the last 20 ns of simulation. However, SA and curcumin always remained complexation status during the simulation. Hydrogen bonds (H-bonds) and hydrophobic interaction were the most critical acting forces involved in the formation and stability of V7-type SA-curcumin complex. Molecular docking presented that H-bonds interaction between curcumin ligand and V7-type SA chain (O3 at the 25th glucose unit, and O6 at the 17th and 20th glucose units) were found. Furthermore, the hydrophobic interactions were discovered between curcumin ligand and SA chain (18th, 19th, 21st, 22nd and 23rd glucose units).